2020
DOI: 10.3390/jcm9093003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond BRCA1 and BRCA2: Deleterious Variants in DNA Repair Pathway Genes in Italian Families with Breast/Ovarian and Pancreatic Cancers

Abstract: The 5–10% of breast/ovarian cancers (BC and OC) are inherited, and germline pathogenic (P) variants in DNA damage repair (DDR) genes BRCA1 and BRCA2 explain only 10–20% of these cases. Currently, new DDR genes have been related to BC/OC and to pancreatic (PC) cancers, but the prevalence of P variants remains to be explored. The purpose of this study was to investigate the spectrum and the prevalence of pathogenic variants in DDR pathway genes other than BRCA1/2 and to correlate the genotype with the clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Recently, Germani et al. 9 carried out a multi-gene panel testing on 113 BRCA -negative patients with BC, OC, or PC, by identifying in 14 patients a PV or a likely pathogenic variant (LPV) beyond BRCA1/2 genes, such as CHEK2 , RAD51C , ATM , MLH1 , MSH2 , and RECQL . Our recent study 10 conducted on patients with bilateral breast cancer (BBC) showed that 14.4% of PVs in high- and moderate-penetrance BC susceptibility genes, such as PTEN , PALB2 , CHEK2 , ATM , and RAD51C , would have been lost in the absence of an analysis carried out via multi-gene panel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Germani et al. 9 carried out a multi-gene panel testing on 113 BRCA -negative patients with BC, OC, or PC, by identifying in 14 patients a PV or a likely pathogenic variant (LPV) beyond BRCA1/2 genes, such as CHEK2 , RAD51C , ATM , MLH1 , MSH2 , and RECQL . Our recent study 10 conducted on patients with bilateral breast cancer (BBC) showed that 14.4% of PVs in high- and moderate-penetrance BC susceptibility genes, such as PTEN , PALB2 , CHEK2 , ATM , and RAD51C , would have been lost in the absence of an analysis carried out via multi-gene panel.…”
Section: Introductionmentioning
confidence: 99%
“…8 In spite of BRCA1 and BRCA2 being the two high-penetrance genes primarily associated with increased risk of hereditary BC/OC and PC, several studies have helped identify many other predisposition genes for these tumours. 9,10 Other hereditary cancer syndromes could be associated with germline PVs in several high-and moderate-risk susceptibility genes such as CDH1, PALB2, PTEN, STK11, TP53, ATM, CHEK2, BARD1, BRIP1, RAD51C, and RAD51D. 10,11 Recently, it has become necessary to study several genes in a short time and in an inexpensive way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the penetrance of large intragenic duplications has not been evaluated or compared to that of other variants. Unfortunately, due to the reduced penetrance and variable expressivity of the cancer susceptibility condition, the absence of large families available for molecular testing and the lack of functional studies, most variants are classified as VUS [ 2 ]. Recently, adjustments of the ACMG variant classification were proposed for CHEK2 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of heterozygous point mutations and intragenic rearrangements of high penetrance genes BRCA1 and BRCA2 in cancer susceptibility (especially, but not only, breast and ovarian cancer) is well established, and international guidelines addressing molecular testing indications and clinical management are available [ 1 ]. Variants in other genes with high and moderate penetrance whose products are involved in the same DNA damage sensing and repair pathway can result in similar cancer susceptibility conditions [ 2 ]. CHEK2 (checkpoint kinase 2; MIM# 604373) is a tumor suppressor gene encoding a serine–threonine kinase involved in DNA repair, cell cycle regulation, senescence and apoptosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%